A comment on Basbøll’s phonological syllabification as applied to Danish - Molbæk Hansen, Peter (Annual Report of the Institute of Phonetics University of Copenhagen, 1979)
Basbøll’s principles for syllabifying phonological strings in Danish are discussed. Certain counterexamples to the predictions of these principles are presented, and it is argued that certain structural properties of Danish words cannot be adequately accounted for by Basbøll’s syllabification strategy in its present form.